REPRESENTASI DIKTATOR DALAM FILM THE INTERVIEW (STUDI SEMIOTIKA ROLAND BARTHES) - Fandy Sandra Rahmadhani; Nita Rimayanti (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2017)
There are Stories in the film that illustrates how A leader of North Korea who is an authoritarian, cruel dictator who oppresses his people to achieve his will. The phenomenon that occurred in this study shows about the assassination attempt against the North Korean president utilizing a TalkShow show to dismantle the ugliness of the North Korean government. This study aims to determine the meaning of dictators based on semiotics analysis Roland Barthes and dictator representation in the movie